Tuning Polyelectrolyte-Surfactant Interactions: Modification of Poly(ethylenimine) with Propylene Oxide and Blocks of Ethylene Oxide - Penfold, J; Thomas, R; Li, P; Batchelor, S; Tucker, I; Burley, A (American Chemical Society, 2016)
Significantly enhanced adsorption at the air-water interface arises in polyelectrolyte/ionic surfactant mixtures, such as poly(ethylenimine)/sodium dodecyl sulfate (PEI/SDS), down to relatively low surfactant concentrations due to a strong surface interaction between the polyelectrolyte and surfactant. In the region of charge neutralization this can result in precipitation or coacervation and give rise to undesirable properties in many applications. Ethoxylation of the PEI can avoid precipitation, but can also considerably weaken the interaction. Localization of the ethoxylation can overcome these shortcomings. Further manipulation of the polyelectrolyte-surfactant interaction can be achieved by selective ethoxylation and propoxylation of the PEI amine groups. Neutron reflectivity and surface tension data are presented here which show how the polyelectrolyte-surfactant interaction can be manipulated by tuning the PEI structure. Using deuterium labeled surfactant and polymer the neutron reflectivity measurements provide details of the surface composition and structure of the adsorbed layer. The general pattern of behavior is that at low surfactant concentrations there is enhanced surfactant adsorption due to the strong surface interaction; whereas around the region of the SDS critical micellar concentration, cmc, the surface is partially depleted of surfactant in favor bulk aggregate structures. The results presented here show how these characteristic features of the adsorption are affected by the degree of ethoxylation and propoxylation. Increasing the degree of propoxylation enhances the surfactant adsorption, whereas varying the degree of ethoxylation has a less pronounced effect. In the region of surfactant surface depletion increasing both the degree of ethoxylation and propoxylation result in an increased surface depletion.